1990
DOI: 10.1007/bf01957687
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency in children: Role of magnetic resonance imaging in assessing aetiopathogenesis and prognosis in idiopathic hypopituitarism

Abstract: To search for the presence of morphostructural abnormalities of the hypothalamus-pituitary region in growth hormone deficient (GHD) children magnetic resonance imaging (MRI) was performed in 30 GHD patients (age 10.09 +/- 3.5 years) and in 15 healthy age-matched controls. MRI demonstrated a significantly small sella and pituitary volume compared to controls and normal literatures values. In 20 patients the structures were extremely small and an abnormal development of the pituitary stalk was observed, and in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Overall, 33% of the children were deficient in 1 or more hormones other than GH, but it was not noted if any of the children with an ACTH deficiency had normal thyroid function. Smaller studies of children with IGHD have reported TSH deficiency rates of 11–50% and ACTH deficiency rates of 6–26% [4,11,12,13]. These studies did not report a cross-tabulation of the coincidence of ACTH and TSH deficiencies either.…”
Section: Discussionmentioning
confidence: 72%
“…Overall, 33% of the children were deficient in 1 or more hormones other than GH, but it was not noted if any of the children with an ACTH deficiency had normal thyroid function. Smaller studies of children with IGHD have reported TSH deficiency rates of 11–50% and ACTH deficiency rates of 6–26% [4,11,12,13]. These studies did not report a cross-tabulation of the coincidence of ACTH and TSH deficiencies either.…”
Section: Discussionmentioning
confidence: 72%
“…Magnetic resonance imaging (MRI) is a non-invasive technique that facilitates good visualization of both the hypophysis and the pituitary stalk (1)(2)(3)(4), thus improving our understanding of the pathophysiology of apparently idiopathic growth hormone deficiency (GHD) (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The gonadotropin deficit would be as common but difficult to confirm in children before puberty. More rarely diabetes insipidus can be observed (Pellini et al, 1990;Mariani, 1992).…”
Section: Discussionmentioning
confidence: 99%